방송CG 활용 사례 분석과 그래픽디자이너의 역할에 관한 연구 - 조풍연(Poong-Yeon Cho) (한국콘텐츠학회 논문지, 21(12), 2021)
In the meantime, broadcasting CG has gone through the process of dismantling, changing, and distorting, while broadcasting CG in broadcasting programs utilizes the expanded background of 'temporality' and 'formality'. This is to create an audiovisual language that appeals to human synesthesia by expressing the meaning to be conveyed in three dimensions. Broadcast CG goes beyond simple instructional and informational broadcast graphic operation, and increases the pure aesthetic value and sensibility of the video considering readability and formativeness, and through this, the audiovisual information perfection of the broadcast program is derived and acts as a very important factor. Therefore, this paper examines the results of broadcast CG production and utilization methods at existing local broadcasters, and identifies the limitations of local broadcasters' CG production and utilization through case analysis for each broadcast program type. We want to derive a model that is a compromise line. In addition, I would like to suggest a plan that can be applied more actively and practically to local broadcasting programs. In order to solve this problem, this study first examines "Analysis of cases of use of broadcasting CG production in broadcasting programs" and then "more efficient broadcasting CG production techniques by identifying problems in broadcasting CG production methods and utilization of local broadcasters" and how to actively use it". In addition, the results of this study are expected to contribute to the establishment of a new role and practical broadcast CG production model for broadcast graphic designers in charge of broadcast CG production and the technical perspective of broadcast program production by local broadcasters. 그동안 방송CG는 해체·변화·왜곡의 과정을 거듭하면서, 방송프로그램에서의 방송CG는 '시간성'과 '조형성'이라는 확대된 배경을 활용한다. 이를 통해 전달하고자 하는 의미를 입체적으로 표현함으로써 인간의 공감각에 호소하는 시청각적 언어를 창조하는 것이다. 방송CG가 단순한 지시적, 정보 전달적인 방송그래픽의 운용을 넘어, 가독성과 조형성을 고려한 영상의 순수한 미적가치와 감성을 증대시키고, 이를 통한 방송프로그램의 시청각정보 완성미를 도출하며 매우 중요한 요소로 작용한다. 따라서 본 논문에서는 기존의 지역방송사에서의 방송CG제작과 활용방법에서 나타난 결과물들을 살펴보고 방송프로그램 유형별 사례분석 통해 그동안 불가피하게 직면했던 지역 방송사들의 CG제작 및 활용의 한계점들을 파악하고, 이를 보완하기 위한 절충선이 되는 모델을 도출하고자 한다. 그리고 지역 방송프로그램에 보다 적극적이고 실용적으로 적용될 수 있는 방안을 제시하고자 한다. 이러한 문제해결을 위해 본 연구에서는 먼저 "방송프로그램에서의 방송CG제작 활용 사례분석"에 대해서 살펴보고, 그 다음으로 "지역 방송사들의 방송CG제작 방법과 활용의 문제점 파악을 통해 보다 효율적인 방송CG제작기법 및 적극적인 활용방법 등을 제언"하고자 한다. 또한 본 연구의 결과가 지역방송사들의 방송프로그램제작의 기술적인 관점과 방송CG제작을 담당하고 있는 방송그래픽디자이너들에게 새로운 역할과 실용적인 방송CG제작모델 정립에 기여할 것으로 기대된다.